2021
DOI: 10.1002/asia.202100682
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Photocatalysis with 4‐Amino‐TEMPO for Selective Aerobic Oxidation of Amines over TiO2 Nanotubes

Abstract: Attaching π‐conjugated molecules onto TiO2 can form surface complexes that could capture visible light. However, to make these TiO2 surface complexes durable, integrating 2,2,6,6‐tetramethylpiperidine‐1‐oxyl (TEMPO) or its analogues as a redox mediator with photocatalysis is the key to constructing selective chemical transformations. Herein, sodium 6,7‐dihydroxynaphthalene‐2‐sulfonate (DHNS) was obtained by extending the π‐conjugated system of catechol by adding a benzene ring and a substituent sodium sulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…78 In 2021, Lang et al reported a unique cooperative photocatalytic system for the aerobic oxidation of amines to imines, including the release of ammonia releasing using dye-TiO2 nanotubes with TEMPO + BF4or 4-NH2-TEMPO as the catalyst. 79,80 Scheme 6. Oxidation of primary and secondary amines to form imines of TEMPO + Clto give N-methylaniline and N-methylformanilide.…”
Section: -1 Oxidative Esterification/amidationmentioning
confidence: 99%
“…78 In 2021, Lang et al reported a unique cooperative photocatalytic system for the aerobic oxidation of amines to imines, including the release of ammonia releasing using dye-TiO2 nanotubes with TEMPO + BF4or 4-NH2-TEMPO as the catalyst. 79,80 Scheme 6. Oxidation of primary and secondary amines to form imines of TEMPO + Clto give N-methylaniline and N-methylformanilide.…”
Section: -1 Oxidative Esterification/amidationmentioning
confidence: 99%
“…These endeavors could lay the foundation for pursuing a Nb 2 O 5 -based alternative. For example, anchoring colorless hydroxynaphthalene ligands onto TiO 2 could implement either selective reduction64,65 or aerobic oxidation reactions [66][67][68]. Therefore, several representative hydroxynaphthalenes were selected for comparison (Fig.3).…”
mentioning
confidence: 99%